Mevalonate kinase deficiency leads to decreased prenylation of Rab GTPases. Issue 10 (5th July 2016) - Jurczyluk, Julie; Munoz, Marcia A; Skinner, Oliver P; Chai, Ryan C; Ali, Naveid; Palendira, Umaimainthan; Quinn, Julian MW; Preston, Alexandra; Tangye, Stuart G; Brown, Andrew J; Argent, Elizabeth; Ziegler, John B; et al.
Abstract : Mevalonate kinase deficiency (MKD) is caused by mutations in a key enzyme of the mevalonate–cholesterol biosynthesis pathway, leading to recurrent autoinflammatory disease characterised by enhanced release of interleukin‐1β (IL‐1β). It is currently believed that the inflammatory phenotype of MKD is triggered by temperature‐sensitive loss of mevalonate kinase activity and reduced biosynthesis of isoprenoid lipids required for the prenylation of small GTPase proteins. However, previous studies have not clearly shown any change in protein prenylation in patient cells under normal conditions. With lymphoblast cell lines from two compound heterozygous MKD patients, we used a highly sensitive in vitro prenylation assay, together with quantitative mass spectrometry, to reveal a subtle accumulation of unprenylated Rab GTPases in cells cultured for 3 days or more at 40 °C compared with 37 °C. This included a 200% increase in unprenylated Rab7A, Rab14 and Rab1A. Inhibition of sterol regulatory element‐binding protein (SREBP) activation by fatostatin led to more pronounced accumulation of unprenylated Rab proteins in MKD cells but not parent cells, suggesting that cultured MKD cells may partially overcome the loss of isoprenoid lipids by SREBP‐mediated upregulation of enzymes required for isoprenoid biosynthesis. Furthermore, while inhibition of Rho/Rac/Rap prenylation promoted the release of IL‐1β, specific inhibition of Rab prenylation by NE10790 had no effect in human peripheral blood mononuclear cells or human THP‐1 monocytic cells. These studies demonstrate for the first time that mutations in mevalonate kinase can lead to a mild, temperature‐induced defect in the prenylation of small GTPases, but that loss of prenylated Rab GTPases is not the cause of enhanced IL‐1β release in MKD.